THE FUTURE CHALLENGES OF MODERATE PESANTREN IN INDONESIA: - Badrus Samsul Fata (Institut Binamadani Indonesia, 2023)
Abstract Moderate Indonesia's Islamic boarding schools (pesantren) and madrasahs are firmly linked with mass organizations like Nahdlatul Ulama (N.U.), Nahdhatul Wathan (N.W.), Perti, Jam'iyyah al-Khairat, Mathla'ul Anwar (M.A.), and others. Moderate pesantrens have developed teaching methods and an educational system that are open, moderate, pluralistic, and even resistant to radical ideology, violent extremism, and terrorism throughout the centuries. Western sociological-anthropological investigations by Bruinessen, Fealy, Barton, Steenbrink, Horikoshi, Ziemek, and Indonesian scholars such as Dhofier, Wahid, Rahardjo, and Mansur Noor supported this, with certain limitations. Dhofier asserted that the Islamic boarding schools and madrasas were unique until the 1970s as alternative educational institutions. They built a community that valued kyai, santri, langgar, pondok, and kitab kuning. However, violent extremism and terrorist acts in Indonesia over more than a decade implicated alumnae of different radical pesantren; four were affiliated with Jamaah Islamiyyah (Al-Islam Lamongan, al-Mukmin Ngruki, Al-Muttaqien Jepara, and Darusy Syahadah Klaten), and the two others (al-Manar and Al-Hikmah) affiliated with Jamaah Ansharus Tauhid (JAT), and Jamaah Ansharus Syariah (JAS). This paper examines and measures moderate pesantren's future challenges, particularly how global Islamic political movements have fueled religious radicalism and fundamentalism in contemporary Indonesia.